2017
DOI: 10.1161/strokeaha.117.017293
|View full text |Cite
|
Sign up to set email alerts
|

P-Wave Indices and Risk of Ischemic Stroke

Abstract: Background and Purpose-Atrial cardiomyopathy is associated with an increased risk of ischemic stroke. P-wave terminal force in lead V 1 , P-wave duration, and maximum P-wave area are electrocardiographic parameters that have been used to assess left atrial abnormalities related to developing atrial fibrillation. The aim of this systematic review and metaanalysis was to examine their values for predicting ischemic stroke risk. Methods-PubMed and EMBASE databases were searched until December 2016 for studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 42 publications
(44 reference statements)
2
37
0
1
Order By: Relevance
“…P-wave dispersion was defined as the maximum difference in PWD. P-wave terminal force in V1 (PTFV1) was defined as the area subtended by the terminal negative component of a biphasic P-wave in lead V1, with the area calculated by multiplication of the duration and depth of the waveform (He et al, 2017). The primary endpoint of this study was new onset persistent or permanent atrial fibrillation (AF).…”
Section: Definitions Data Extraction Electrocardiographic Measuremementioning
confidence: 99%
See 1 more Smart Citation
“…P-wave dispersion was defined as the maximum difference in PWD. P-wave terminal force in V1 (PTFV1) was defined as the area subtended by the terminal negative component of a biphasic P-wave in lead V1, with the area calculated by multiplication of the duration and depth of the waveform (He et al, 2017). The primary endpoint of this study was new onset persistent or permanent atrial fibrillation (AF).…”
Section: Definitions Data Extraction Electrocardiographic Measuremementioning
confidence: 99%
“…P-wave terminal force in V1 (PTFV1), P-wave duration (PWD), and P-wave area. Adapted from (He et al, 2017) with permission. stenosis severity), log(age * P-wave area in v3).…”
Section: Statistical Analysis Non-linear Variables and Decision Trementioning
confidence: 99%
“…Very long P-wave duration in the top fifth percentile is associated with doubling of risk of AF ( 23 ). A recent pooled meta-analysis showed that prolonged maximum PWD (evaluated as a categorical variable) increases the risk of ischemic stroke ( 24 ). In particular, a previous study demonstrated that in patients with advanced interatrial block there is 1.7-fold increase in the risk of ischemic stroke ( 39 ) and this association resulted not attenuated by incident AF events: this evidence suggests that left atrial disease evaluated by means of P wave duration, is possibly an independent risk factor for ischemic stroke.…”
Section: Ecg Markers Of Atrial Cardiopathy and Influences Of Autonomimentioning
confidence: 99%
“…PWA is considered a marker of abnormal atrial structure and left atrial enlargement. In the ARIC study, mean P wave area was a predictor of AF ( 49 ), in a recent pooled meta-analysis, higher maximal PWA increases of 10% the risk of incident stroke ( 24 ).…”
Section: Ecg Markers Of Atrial Cardiopathy and Influences Of Autonomimentioning
confidence: 99%
See 1 more Smart Citation